Science et Fiction - Annie Escuret (Cahiers Victoriens et Edouardiens)
The relationships between science and fiction are the object of epistemocriticism which is interested in the meeting points between literary works and fields of knowledge in a general way and between science and fiction in particular. Science and literature were the two passions of the 19th century, which was characterized by the conflict between the naturalist and positive scientists on the one hand, and the Romantics and symbolists on the other hand. Among the happy epistemocritics, we will find famous French names such as Michel Serres, Henri Atlan, Michel Foucault and many others. This essay first seeks to delineate the main epistemological turning points in the 19th century. The works of Jane Austen exemplify the triumph of Newtonian episteme. Another refusal of randomness can be found in George Eliot’s works which advocate a conservative reformist organicism. Another paradoxical figure of the century is Charles Dickens whose works foreground outdated scientific knowledge rather than Darwin’s evolutionary theory. This essay also studies other great figures of the century like Meredith, Hardy and Wells. As a conclusion and with a view to enlarging the debate are mentioned a few famous names of 19th–century French literature which were also concerned with the relationships between science and fiction.